2020
DOI: 10.1155/2020/9641904
|View full text |Cite
|
Sign up to set email alerts
|

Application of Acupuncture to Attenuate Immune Responses and Oxidative Stress in Postoperative Cognitive Dysfunction: What Do We Know So Far?

Abstract: Postoperative cognitive dysfunction (POCD) is a common sequela following surgery and hospitalization. The prevention and management of POCD are important during clinical practice. POCD more commonly affects elderly patients who have undergone major surgery and can result in major decline in quality of life for both patients and their families. Acupuncture has been suggested as an effective intervention for many neurological disorders. In recent years, there are increasing interest in the use of acupuncture to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“… 30 General anesthesia combined with surgical shock can change the physiological function of elderly patients. 31 Under the stimulation of a stress response, a series of adverse cardiovascular and cerebrovascular events can easily cause cognitive dysfunction in elderly patients. 32 It is generally believed that three factors contribute to the pathogenesis of POCD: (1) The influence of surgical factors on the internal environment, such as the size of the surgical wound, the duration of the operation, and patient responses related to stress, micro thromboembolism, blood loss, and fluid loss 33 ; (2) The effects of anesthetics on the patient, such as effects of general anesthetics on the CNS and effects of anesthetics on the homeostatic processes of the body, such as hypotension, hypertension, bradycardia, and hypothermia 34 ; (3) The pathophysiological status and social factors of the patient undergoing surgery; for example, advanced age, combined diabetes, hypertension, and cognitive impairment before surgery correlate with POCD occurrence.…”
Section: Discussionmentioning
confidence: 99%
“… 30 General anesthesia combined with surgical shock can change the physiological function of elderly patients. 31 Under the stimulation of a stress response, a series of adverse cardiovascular and cerebrovascular events can easily cause cognitive dysfunction in elderly patients. 32 It is generally believed that three factors contribute to the pathogenesis of POCD: (1) The influence of surgical factors on the internal environment, such as the size of the surgical wound, the duration of the operation, and patient responses related to stress, micro thromboembolism, blood loss, and fluid loss 33 ; (2) The effects of anesthetics on the patient, such as effects of general anesthetics on the CNS and effects of anesthetics on the homeostatic processes of the body, such as hypotension, hypertension, bradycardia, and hypothermia 34 ; (3) The pathophysiological status and social factors of the patient undergoing surgery; for example, advanced age, combined diabetes, hypertension, and cognitive impairment before surgery correlate with POCD occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…POCD refers to the absence of mental disorders and abnormal brain function in elderly patients after surgery, referring to such as mental disorder, anxiety, personality changes and memory impairment [26]. General anesthesia combined with surgical shock can change the physiological function of elderly patients [27]. Under the stimulation of stress response, a series of adverse cardiovascular and cerebrovascular events can easily cause the occurrence of cognitive dysfunction in elderly patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the inflammatory response to anesthesia and surgery may be involved into the incidence of POCD. [2][3][4][5] Note that intestinal microbiota perturbation-induced inflammatory response after surgical trauma has been revealed to play an important role in the pathogenesis and progression of cognitive dysfunction. 6 The gut-brain axis, which is formed by the central nervous system, the enteric innervation that includes extrinsic fibers of the autonomous nervous system and intrinsic neurons of the enteric nervous system, the HPA-axis and the intestinal microbiota, may provide a fresh perspective between inflammatory response and subsequent cognitive decline.…”
Section: Introductionmentioning
confidence: 99%